2021
DOI: 10.1038/s41467-021-21008-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy in deceptive vocal exaggeration of human body size

Abstract: How can deceptive communication signals exist in an evolutionarily stable signalling system? To resolve this age-old honest signalling paradox, researchers must first establish whether deception benefits deceivers. However, while vocal exaggeration is widespread in the animal kingdom and assumably adaptive, its effectiveness in biasing listeners has not been established. Here, we show that human listeners can detect deceptive vocal signals produced by vocalisers who volitionally shift their voice frequencies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 55 publications
2
25
2
Order By: Relevance
“…We showed that both singers and controls can volitionally modulate vocal parameters in a goal-directed fashion to imitate voices of different sizes and pitches, in line with previous work investigating volitional vocal size exaggeration [16][17]. Specifically, we showed that both groups adjusted F0 downward and upward to imitate lower-and higher-pitched voice targets, respectively and, for the first time, we also showed that modulations to imitate longer and shorter VTLs were achieved via appropriate upward and downward movements of the larynx in the vocal tract.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We showed that both singers and controls can volitionally modulate vocal parameters in a goal-directed fashion to imitate voices of different sizes and pitches, in line with previous work investigating volitional vocal size exaggeration [16][17]. Specifically, we showed that both groups adjusted F0 downward and upward to imitate lower-and higher-pitched voice targets, respectively and, for the first time, we also showed that modulations to imitate longer and shorter VTLs were achieved via appropriate upward and downward movements of the larynx in the vocal tract.…”
Section: Discussionsupporting
confidence: 89%
“…A region of left somatomotor cortex identified in the whole participant group did not correspond topographically to previous reports of the larynx motor cortex (LMC). However, a further direct comparison of singers and controls revealed an expertise-related enhancement of VTL representation in right somatosensory cortex, just posterior to the reported location of the dorsal LMC in humans [16][17][18] and in line with a postcentral site previously linked to singing experience [33][34][35]. We speculate that this dorsal site could represent a larynx sensory cortex that is closely coupled to its corresponding LMC during speech motor control [9]: in line with this, probabilistic diffusion tractography analyses of LMC connectivity have revealed dramatically stronger connectivity with somatosensory and inferior parietal cortices in humans than in macaques [46].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In humans, in addition to a permanently descended larynx [7], men and women in diverse cultures can effectively exaggerate their size by volitionally lowering their vocal tract resonances (formants) as well as their fundamental frequency ( f 0 , perceived as voice pitch) [3,8]. In turn, human listeners systematically associate low voice pitch with a large size and physical prowess [9,10].…”
Section: Introductionmentioning
confidence: 99%